Becoming a young adult with cerebral palsy. (September 2019) - Pizzighello, Silvia; Pellegri, Alda; Vestri, Alec; Sala, Marco; Piccoli, Sara; Flego, Loredana; Martinuzzi, Andrea
Abstract: Aims: This paper aims to describe the functioning profile of a clinical sample of patients with Cerebral Palsy at the time of transition. Methods and procedure: For this retrospective observational study, we considered data concerning 389 patients born from 1967 to 1997 with a diagnosis of CP and discharged at the age of 18 ± 3 from "La Nostra Famiglia" Children Care Centres. We reported data concerning: identifiable risk factors, the type of CP, the level of motor, manual and communication abilities, the occurrence of associated impairments and environmental factors, and examine the trends over the decades. Outcome and results: The disorder was mainly bilateral (86%): 57% of patients had quadriplegia and 43% had diplegia. Most of patients had a spastic disorder (86%). Comorbidities were frequent, mainly intellectual developmental disorder (63.5%). One fifth of patients showed a severe impairment of motor, manual and communicative skills in addition to a severe intellectual development disorder. Over decades, the outcome as expressed by the motor functioning profile improved but the outcome as expressed by the global functioning profile worsened because of the growing number of severe multi-disabilities. Conclusion and implication: Knowledge about the functioning profile of young adults with cerebral palsy can support health services in the provision of developmentally appropriate care.